Negligence in Robotic Surgery: Establishing Duty of Care in Legal Cases - Gautam, Purnima; Sharma, Rituja (Journal of Neonatal Surgery, 2025)
The incorporation of cutting-edge technologies, such as robotic surgery, artificial intelligence-driven diagnostics, and automated medical devices, is bringing about a revolution in the healthcare industry, but it also brings about substantial legal issues. The duty of care, which is a fundamental premise in the practice of medicine, needs to develop in order to accommodate these developments while simultaneously assuring the safety of patients and maintaining ethical standards. In the context of high-tech medical practices, the ever-evolving legal doctrines and the obligations of healthcare professionals, technology developers, and institutions are being discussed. It addresses difficulties such as establishing the scope of duty of care, the complications of various stakeholders participating in patient care, and the legal ramifications of artificial intelligence and automation in the healthcare industry. The transition toward product liability frameworks for medical technologies, with a special emphasis on robotic surgery. For the purpose of better managing the junction of technology and medicine, it is proposed that recommendations be made for improving legal and ethical oversight. These recommendations include the establishment of robust regulatory frameworks and the improvement of training for healthcare workers. The importance of dynamic legislative norms that guarantee both innovation and patient protection is emphasized in the chapter which highlights the fact that technological advancements are continuing. A method that involves collaboration between specialists in the fields of law, medicine, and technology in order to protect the rights of patients in a healthcare setting that is becoming increasingly automated.